Therapeutic monitoring of pediatric transplant patients with conversion to generic tacrolimus - Natalia Riva; Paulo Cáceres Guido; Nieves Licciardone; Oscar Imventarza; Marta Monteverde; Raquel Staciuk; Alberto Charroqui; Paula Schaiquevich (Farmacia Hospitalaria)
p>Objective: Therapeutic monitoring during interchange of tacrolimus commercial formulations is essential to ensure similar exposure in transplant patients. However, there are limited data in the pediatric transplant population. This study aims to evaluate exposure, safety and efficacy in maintenance pediatric transplant patients under generic tacrolimus substitution. Method: Pediatric patients who underwent interchange of tacrolimus formulations were detected by the Service of Pharmacy and included in this study. Tacrolimus trough levels (C0), laboratory parameters and clinical characteristics were recorded before and after the switch. Statistical analysis was performed using Wilcoxon matched pair t-test. Results: In total, 10 patients with kidney, liver, heart and hematopoietic stem cell transplantation received the innovator and switched to the generic product. The median (range) of the C0 normalized by the dose before and after switch was 74.8 [(ng/ml)/(mg/kg)] (13.8-518.4) and 65.1 [(ng/ml)/(mg/kg)] (13.5-723.5), respectively (p>0.05). Tacrolimus dose was 0.070(mg/kg) (0.024-0.461) and 0.069(mg/kg) (0.017- 0.571) for the innovator and generic formulation, respectively, with no difference when comparing both values (p>0.05). Laboratory parameters did not change after conversion (p>0.05). Adverse events, acute rejection, death and graft loss were not observed. Conclusion: In our study population, no significant differences in terms of laboratory parameters, drug exposure and dose were observed. We emphasize the need of close monitoring to ensure a safe interchange, especially in vulnerable populations such as the pediatric.